Should countries auction immigrant visas? - Madeline Zavodny (IZA World of Labor, 2015)
Many immigrant destination countries face considerable pressure to change their immigration policies. One of the most innovative policies is auctioning the right to immigrate or to hire a foreign worker to the highest bidders. Visa auctions would be more efficient than current ways of allocating visas, could boost the economic contribution of immigration to the destination country, and would increase government revenues. However, visa auctions might weaken the importance of family ties in the migration process and create concerns about fairness and accessibility. No country has yet auctioned visas.
Keywords: J61; J68; 330; auction; visas; immigrants